Estudio de las propiedades electrónicas y magnéticas del sistema con estructura doble perovskita Sr2Fe1+xMo1-xO6 mediante cálculos de primeros principios - Reyes Úsuga, Abdul Mauricio (My University, 2015)
The introduction of spin as an extra degree in electronics has given birth to a brand new paradigm to explore potential applications based on the quantum magnetic properties of materials. Phenomena such as colossal magnetoresistance and the enormous decreasing of resistance in response to a magnetic eld applied to an oxides with double perovskite structure, which has led to a systematic studies of his electric and magnetic properties. In this work we show a theoretical study of the ordered stoichiometric and non-stoichiometric double perovskite Sr2Fe1+xMo1-xxO6 in the range 􀀀1 x < 1=3, and the disordered system at 25 %, to determinate changes in lattice parameters, volume, electric and magnetic properties. We built crystalline double perovskite structures of 20, 40 and 80 atoms, using the Generalized Gradient Approximation (GGA) +U with relativistic scalar pseudopotentials Perdew-Burke-Ernzerhof (PBE) into the Density Functional Theory (DFT). To carry out the work mentioned above we used the Quantum Espresso codes. By relaxation structure of supercells, we obtained the lattice parameters and volume. Besides we done a Density of States (DOS) calculations to describe the electronic and magnetic properties of each composition system. Our results are in accordance with previous half-metallic calculations and is sensitive to a variations of the composition and anti-site (AS) defects in the ground state.
Facultad de Ciencias Físico Matemáticas. Maestría en Ciencias en Ingeniería Física
Keywords: info:eu-repo/classification/cti/1